2018
DOI: 10.1155/2018/5423961
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Rescues Cognitive Impairment and Upregulates Dopamine-β-Hydroxylase Expression in Chronic Cerebral Hypoperfusion Rats

Abstract: Alteration of dopamine (DA) and noradrenaline (NA) contributes to cognitive function. Acupuncture has been shown to affect DA and NA in chronic cerebral hypoperfusion (CCH) rats. However, the effect of acupuncture on DA-β-hydroxylase (DBH), the biosynthetic enzyme of NA, remains unknown. In CCH rats we established chronic hypoperfusion by bilateral common carotid artery occlusion (two-vessel occlusion, 2VO) and treated them with acupuncture. Acupuncture displayed beneficial effects on hippocampus-dependent mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The effectiveness and safety of acupuncture for TS has been confirmed by numerous clinical studies (Wu et al, 1996; Ma et al, 2006; Zhu et al, 2009; Tang et al, 2015; Yu et al, 2016; Lee, 2017), but the underlying mechanisms remain unclear. Previous studies have demonstrated that acupuncture can regulate the DA system (Bo et al, 2017; Lin et al, 2017; Kim et al, 2018; Xiao et al, 2018). DA plays an important role in the recovering effect of acupuncture on motor functions (Cabyoglu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness and safety of acupuncture for TS has been confirmed by numerous clinical studies (Wu et al, 1996; Ma et al, 2006; Zhu et al, 2009; Tang et al, 2015; Yu et al, 2016; Lee, 2017), but the underlying mechanisms remain unclear. Previous studies have demonstrated that acupuncture can regulate the DA system (Bo et al, 2017; Lin et al, 2017; Kim et al, 2018; Xiao et al, 2018). DA plays an important role in the recovering effect of acupuncture on motor functions (Cabyoglu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…And converging studies supported a crucial role of LTD in some types of learning and memory and in situations where cognitive demands require a flexible response [ 59 ]. Many electrophysiological studies showed that acupuncture could apparently improve the recovery from cognitive deficits by promoting LTP and/or LTD [ 61 63 ] and preventing or restoring the impaired LTP [ 64 69 ] in AD or VCI rat models. In addition to LTP and LTD, EA could also ameliorate the synaptic transmission by raising the slope of excitatory postsynaptic potential (EPSP) and the amplitude of population spikes (PS) in an AD mouse model [ 70 ].…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…Cholinergic system in the brain, especially the basal forebrain projections to the hippocampus and cortex, is responsible for memory and learning (Cain, 1998) and is known to be affected in AD (Whitehouse et al., 1981). Noradrenaline (NA) is related to various cognitive and physiological processes, including learning and memory (Xiao et al., 2018; Zhu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%